2016 Romanian regional elections report. Issue 3 (27th May 2018) - Dragoman, Dragos; Zamfira, Andreea
ABSTRACT: Regional elections in Romania are more important politically than it would generally be the case in a highly centralized country. Despite the limited regional autonomy of the territorial units named județe (counties) which host those elections, regional elections have become more and more important because of their electoral forecasting potential. As explained in this elections report, county elections have grown up as barometer elections, turning, through their capacity to accurately indicate the outcome of the national elections into a 'subspecies' of second-order elections. The report will therefore emphasize their special relationship with national elections due to election timing, constituency design and electoral formula similarities. Finally, the report evaluates the 2016 elections outcomes, by strengthening the concept of barometer elections as a type of second-order elections in the framework of a highly nationalized party-system.